Macro-micro analysis method for wave propagation in stochastic media. - Ichimura, T.
This paper presents a new analysis method, called macro?micro analysis method (MMAM) for numerical simulation of wave propagation in stochastic media, which could be used to predict distribution of earthquake strong motion with high accuracy and spatial resolution. This MMAM takes advantage of the bounding medium theory (BMT) and the singular perturbation expansion (SPE). BMT can resolve uncertainty of soil and crust structures by obtaining optimistic and pessimistic estimates of expected strong motion distribution. SPE leads to efficient multi-scale analysis for reducing a huge amount of computation. The MMAM solution is given as the sum of waves of low resolution covering a whole city and waves of high resolution for each city portion. This paper presents BMT and SPE along with the formulation of MMAM for wave propagation in three-dimensional elastic media. Application examples are presented to verify the validity of the MMAM and demonstrate potential usefulness of this approach. In a companion paper (Earthquake Engng. Struct. Dyn., this issue) application examples of earthquake strong motion prediction are also presented.
Keywords: Earthquake strong motion prediction; Multi-scale analysis; Uncertainty; Stochastic modelling; Bounding media; Macro?micro analysis method